Melanocyte development and malignant melanoma. - Goding, C (2000)
Malignant melanoma is a notoriously aggressive disease that can affect relatively young individuals and whose incidence is rising at an alarming rate. Unlike many cancers, metastatic melanoma is poorly responsive to current therapies and mutations affecting p53, the retinoblastoma gene product or Ras which occur frequently in many other cancer types, appear to be rare or at least relatively late events in the progression of the disease. Recent advances in our understanding of the disease at the molecular level have indicated that in addition to the loss of cell cycle checkpoints which may be common to all cancers, malignant melanoma shares many characteristics in common with developmental precursors to melanocytes, the mature pigment producing cells of the skin and hair follicles which are responsible for skin and hair colour. This review therefore focuses on the signalling pathways that play a crucial role in the development of the melanocyte lineage which are subject to deregulation in malignant melanoma namely signalling by receptor tyrosine kinases, the Wnt signalling pathway, as well as loss of the p16INK4a cyclin-dependent kinase inhibitor. Intriguingly all three pathways impact on the expression or function of the microphthalmia-associated transcription factor which plays an essential role in melanocyte development.